Making citizen’s charter effective in public organizations of Bangladesh: Rhetoric or reality? A study of department of immigration and passports - Razzaque, Farhana (The University of Bergen, 2022)
This thesis submitted in partial fulfillment of the requirements for the degree of Master of Philosophy (M. Phil) in Public Administration Submitted to Department of Administration and Organization Theory University of Bergen